PERLINDUNGAN BAGI TENAGA KERJA MIGRAN INDONESIA TERHADAP TINDAKAN HUMAN TRAFFICKING DI WILAYAH TIMUR TENGAH DITINJAU DARI HUKUM INTERNASIONAL - Andika Dwi Yuliardi; Aslan Noor; Andrew Christian Banjarnahor; Abdillah Bararah; Azhar Nur Fauzi (Prodi Ilmu Hukum, Universitas Teuku Umar, 2021)
Indonesia still has a very crucial problem, the problem is human trafficking. This study is aimed at identifying and analyzing legal protection for Indonesian workers who work in the Middle East against crimes of trafficking in persons based on national law and international law as well as the application of sanctions given to perpetrators. The research method in this article is juridical normative using a statute approach and a conceptual approach. The results of this study are a form of protection for migrant workers, there are several international regulations, one of which is CEDAW. Meanwhile, the government's efforts in legal protection for TKI victims of human trafficking are by issuing various legal instruments, one of which is the UU PTPPO (Pemberantasan Tindak Pidana Perdagangan Orang). From this research, it can be concluded that the government needs to collaborate bilaterally, as well as multilaterally, especially the destination countries for placing Indonesian migrant workers, and cooperate with non-governmental organizations in combating human trafficking.